2014
DOI: 10.1007/s10735-014-9587-y
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of the Notch family in the human endometrium of fertile and infertile women

Abstract: To investigate the spatial and temporal immunolocalisation and staining intensity of the Notch signalling family in endometrium of fertile and infertile women, endometrial biopsies were collected by curettage from 25 fertile women across the menstrual cycle and 10 infertile women in the mid secretory phase of menstrual cycle. Immunohisotchemistry was completed for NOTCH1, -2, -3, -4, cleaved Notch, DLL1, -3, -4, JAGGED1, -2, HES and NUMB and immunostaining intensity measured in both the endometrial glandular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…Strong cytoplasmic immunostaining for Numb was limited to the epithelial cells and very weak staining was observed in the stroma. Contrasting results have been reported, suggesting either consistent levels across the menstrual cycle [ 114 ] or decreased immuno-expression in the mid secretory phase [ 118 ]. These studies only utilized single technique (IHC) without any secondary confirmatory techniques or functional work [ 114 ].…”
Section: Examining Endometrium For the Expression Of Putative Stemmentioning
confidence: 64%
See 1 more Smart Citation
“…Strong cytoplasmic immunostaining for Numb was limited to the epithelial cells and very weak staining was observed in the stroma. Contrasting results have been reported, suggesting either consistent levels across the menstrual cycle [ 114 ] or decreased immuno-expression in the mid secretory phase [ 118 ]. These studies only utilized single technique (IHC) without any secondary confirmatory techniques or functional work [ 114 ].…”
Section: Examining Endometrium For the Expression Of Putative Stemmentioning
confidence: 64%
“…This immuno-expression was dynamic in the endometrium, with higher Notch1 in the proliferative phase than in the secretory phase in some studies [ 114 , 117 ], although the reverse was reported in others [ 115 ], while no significant difference was observed between the proliferative phase in pre-menopausal and postmenopausal samples. Interestingly, the maximal staining intensity was seen in the mid secretory receptive phase of the menstrual cycle [ 118 ]. Strong cytoplasmic immunostaining for Numb was limited to the epithelial cells and very weak staining was observed in the stroma.…”
Section: Examining Endometrium For the Expression Of Putative Stemmentioning
confidence: 99%
“…Using String and Cytospace online tools, genes in these clusters were mapped into an interaction network ( Figure 4E and Supplementary Figure S2). Strikingly, we found genes including catenin beta 1 (CTNNB1), NOTCH1 (notch receptor 1), and GJA1 (gap junction protein, alpha), which are well-known regulators of endometrial receptivity (Zhang et al, 2012;Van Sinderen et al, 2014;Winterhager and Kidder, 2015;Su et al, 2016;Yu et al, 2017;Zheng et al, 2017), centered in this network. In addition, transcripts of EPHA2 (EPH Receptor A2), IL6ST (Interleukin 6 Signal Transducer), JAG1 (Jagged canonical notch ligand 1), MSX1 (msh homeobox 1), PLA2G4A (phospholipase A2, group IVA), TGFB1 (transforming growth factor beta 1), SPHK1 (sphingosine kinase 1), and VANGL2 (VANGL planar cell polarity protein 2) exhibited > 1.5-fold change of expression (red dot), which have been proved functional in the endometrial receptivity regulation.…”
Section: Knockdown Of Cdyl Affected the Migration Ability And Transcrmentioning
confidence: 95%
“…In early pregnancy, the Notch signaling pathway functions through cell-cell interactions to regulate stem cell renewal and differentiation, decidualization, implantation, placentation, and angiogenesis (84). Notch1 protein expression is higher in the mid-secretory (receptive phase) endometrium of fertile women, compared to infertile women (85). Thus, DNER may be important for maternal embryonic/fetal communication leading to appropriate placentation and downregulation of DNER in IVF pregnancies may impact this communication.…”
Section: Discussionmentioning
confidence: 99%